2023
DOI: 10.1002/rcr2.1147
|View full text |Cite
|
Sign up to set email alerts
|

Tezepelumab treatment for allergic bronchopulmonary aspergillosis

Abstract: An 82‐year‐old man had been diagnosed with asthma. He experienced repeated exacerbations requiring treatment with a systemic corticosteroid despite being treated with medications including high‐dose fluticasone furoate/umeclidinium/vilanterol, montelukast sodium, and theophylline; treatment with mepolizumab was then initiated. The patient had been free from exacerbations for 15 months; however, he suffered from post‐obstructive pneumonia and atelectasis secondary to mucoid impaction in the right middle lobe of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Omalizumab is a potential therapeutic approach since ABPA is associated with elevated IgE levels. Mepolizumab (anti-IL-5), benralizumab (anti-IL-5R), dupilumab (anti-IL-4Rα) and tezepelumab (anti-TSLP) have also been used in ABPA patients [ 135 , 142 , 162 165 ]. Most experience of biological agents in ABPA is with omalizumab.…”
Section: Resultsmentioning
confidence: 99%
“…Omalizumab is a potential therapeutic approach since ABPA is associated with elevated IgE levels. Mepolizumab (anti-IL-5), benralizumab (anti-IL-5R), dupilumab (anti-IL-4Rα) and tezepelumab (anti-TSLP) have also been used in ABPA patients [ 135 , 142 , 162 165 ]. Most experience of biological agents in ABPA is with omalizumab.…”
Section: Resultsmentioning
confidence: 99%
“…Biologics are not currently available for ABPM cases. Case reports and series have reported that the use of biologics targeting IgE, 24 IL‐5, 25 IL‐4/IL‐13, 26 , 27 , 28 , 29 , 30 , 31 , 32 and TSLP 33 improves the disease status of ABPA complicated by severe asthma. Monoclonal antibodies against IgE have therapeutic efficacy in patients with ABPA and severe asthma, including 12 of the 25 patients with NTM‐PD.…”
Section: Discussionmentioning
confidence: 99%